Perception of local tourists towards safety practices in Malacca city - Ismail, Lisa Mariam Syawal; Tukiran, Nor Anis Intan Aqiah; Zakariah, Siti Hajar; Ahmad, Nor Aziah (GAE, 2021)
Safety practices of tourism products have been a huge reason to choose from. Lacking of good safety practices might become disadvantages for the tourism industry. This study aims to examine the perception of local tourists on the safety practices applied by the tourism industry. The perception has been examined on the three aspect, (1) safety practices in terms of accommodation; (2) safety practices in terms of accessibility; and (3) enforcement practices by local authorities. A total of 30 respondents consists of local tourists that visited Malacca City were involved. Descriptive analysis of mean and percentage was employed to test the objectives. The results showed that local tourists were concerns of the accommodation quality with mean of 4.03, make sure the vehicles were safe to access with mean of 3.97 and local tourist feel safer with local enforcement with mean of 4.06. Undeniable the safety practices of the tourism industry do give popular concerned among the local tourists.